Pengaruh Kompensasi, Disiplin Kerja, Dan Motivasi Terhadap Produktivitas Kerja Pegawai Pada Dinas Ketahanan Pangan Provinsi Jambi - Rindi Antika; Dahmiri; Ovie Yanti (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of compensation, work discipline, and motivation on employee work productivity at the Jambi Province Food Security Service. The background of this study is based on the importance of productive human resources, where adequate compensation, high work discipline, and strong motivation are believed to be the main factors in increasing employee productivity. The research method used is quantitative with a survey approach, where data is collected through questionnaires distributed to all civil servants of the Jambi Province Food Security Service. Data analysis was carried out using multiple linear regression to determine the simultaneous and partial effects of the three independent variables on work productivity. The results of the study indicate that compensation, work discipline, and motivation have a positive and significant effect on employee work productivity simultaneously (F). This study confirms that increasing compensation, enforcing work discipline, and strengthening work motivation are very important to encourage employee productivity in government agencies. This study is expected to be a reference for the Jambi Province Food Security Service in formulating policies that support improving employee performance in order to achieve organizational goals optimally.